Country Path - Branch Cultural Historical Association (2008)
Footpaths leading out from the Place have been created over the years as hunters, anglers, berry pickers and hikers have walked to and from their favourite spots. The Country Path opens up the area known as the Country, north and east of the River. Other paths include the Bear Path, Boggy Path, Manning's Path, the Mash Path and the Stick of Plank Path.